The The Effect Of Digital Banking Quality On Service Satisfaction For Users At Bank Syariah Indonesia - Albanjari, Muhammad Faisal; Nafidzi, Elman; Maharani, Dewi (Tawazuna, 2023)
This research was conducted to determine the effect of Quality Design, Accuracy, Speed and Security on service satisfaction for UM Banjarmasin students. This research was conducted on UM Banjarmasin students class of 2019, whose sample amounted to 79 students. The data source was obtained through questionnaires distributed to respondents and processed again using IBM SPSS 23 software, using Multiple Linear Regression tests and this study used quantitative methods. The results showed that the value of Sig. Variable Quality Design (X1), amounted to 0.04 < 0.05 and thitung 2.967 > 1.993 ttabel, Sig. Variable Accuracy (X2), amounted to 0.245 > 0.05 and thitung 1.173 < 1.993 ttabel, Sig. Variable Speed (X3) value of 0.025 < 0.05 and thitung of 2.284 > 1.993 ttabel, and Sig. Variable Security (X4) of 0.000 < 0.05 and thitung of 4.945 > 1.993 ttabel. The results showed that simultaneously the variables Quality Design, Accuracy, Speed, and Security had a positive effect on service satisfaction for UM Banjarmasin students. This can be seen by the Sig. value of 0.000 < 0.05 and the Fhitung value of 30.813 > 2.73 Ftabel.